Life Cycle Assessment as a complementary utility to regulatory measures of shipping energy efficiency. (1st December 2016) - Blanco-Davis, Eduardo; Zhou, Peilin
Abstract: The purpose of this paper is to document that LCA, aside from showing indication of compliance to both current IMO regulatory metrics (i.e. EEDI and EEOI) –not only as a practical environmental indicator, but also as a tool able to highlight energy efficiency–, can also be used in parallel to these, serving as a complementary utility able to assist with their practical implementation. An LCA model formulation is summarised and also applied on a case study vessel, utilising it for validation, and additionally for comparing the LCA approach to the IMO regulatory metrics. Results show that aside from the environmental score of CO2 emissions per unit of work –recognised by the current regulatory metrics–, LCA can also offer NOx and SOx scores, along with other hazardous releases. Moreover, LCA –aside from showing compliance to the formulation of both IMO regulatory metrics– is able to present material and energy utilisation throughout different stages within the vessel's lifetime. Lastly, it is documented that LCA can be used in parallel to the regulatory metrics, in order to efficiently emphasise detailed environmental information. Furthermore, the implementation of LCA could be considered as a potential aid for the European Commission's recent MRV legislation. Highlights: LCA is increasingly used to evaluate issues related to shipping. The possibility to apply LCA in parallel to other regulatory metrics is stressed. LCA is emphasised as an aid in the application of the EEDI and EEOI.